Freie Norddeutsche "Clavierstücke Pedaliter" zwischen Orgel und Saitenclavieren - Miklavčič, Dalibor (Muzikološki zbornik, 2011)
Baroque North German 'free keyboard music pedaliter' does not necessarily represent exclusive organ music. Structural differences between choral repertoire and pedaliter free works show them as two separate genres, choral works being genuine organ music, free works belonging rather to the idiom of clavichords or harpsichords with pedals. New parameters for the performance practice of this repertoire arise.
Keywords: idiom; northgerman baroque music; organ tuning; pedaliter; severno nemška baročna glasba; stringed keyboard instruments with pedal; strunska klaviaturna glasbila s pedalom; uglasitve orgel